Empirical evidence for intransitivity in consumer preferences - Guadalupe-Lanas, Jorge (2020)
Consumer preferences patterns; Edible and nonedible goods; Transitivity assumption; Preference reversal phenomenon; Strong and weak transitivity, Behavioral economics; Money; Macroeconomics; Econometrics; Experimental economics. © 2020The present paper addresses one of the most important assumptions in consumer preference patterns: transitivity. This assumption states that, logically, selections between goods are rational because of the transitivity statement, which posits that people always prefer goods in the following order: A is preferred to B, and B is preferred to C, so A is preferred to C. With the aim of proving this principle's validity, we conducted an experiment with 70 subjects and probed their preferences in relation to edible and nonedible goods. We used a survey methodology, which allowed us to analyze three distinct situations: 1) individuals faced with goods choices without restrictions; 2) individuals facing budget restrictions and price changes; and 3) individuals faced with decreased disposable income. The results mostly showed that there was no evidence of transitivity in consumer preferences. On average, transitivity appeared in only 8% of the sample, and in cases where transitivity was proved, it was revealed to be strong. The preferences were transitive primarily in relation to edible rather than nonedible goods. © 2020